Protection of Civil Rights of Children of Mixed Marriages in Cross-Border Business Asset Inheritance Disputes: A Review from the Perspective of Lex Rei Sitae - Indah Riyanti; Mardi Chandra (Universitas Islam Sultan Agung, 2026)
Mixed marriages carry complex civil legal consequences, particularly regarding the protection of children's rights in the inheritance of cross-border business assets. This study aims to analyze the synchronization of limited dual citizenship regulations with sectoral laws in Indonesia and to evaluate the effectiveness of the Lex Rei Sitae principle in ensuring legal certainty and justice for children. Using a combined legal research method (normative-empirical), data was collected through a literature review of international and domestic legal instruments and in-depth interviews with legal practitioners to capture the challenges in the field. The results indicate a disharmony between the Citizenship Law and agrarian and investment laws, leading to the degradation of children's economic rights due to rigid restrictions on foreign asset ownership. The Lex Rei Sitae principle provides certainty of property status but tends to ignore children's absolute rights (legitieme portie) due to the weak mechanism for recognizing transnational inheritance documents. This study recommends the formulation of preventative legal protection through optimizing marriage agreements and local wills, as well as the need for bureaucratic policy reform that integrates the principle of the best interests of the child into cross-border business asset administration procedures.